Utilizing Recycled Rubber and Municipal Waste Incineration Fly Ash in Cement-Stabilized Clayey Soils - Aouf, Gehan; Alhakim, Ghida; Jaber, Lina (Civil Engineering Journal, 2024)
This study explores an innovative approach combining municipal solid waste incinerator fly ash (MSWIFA), cement, and recycled rubber to enhance soil properties. The research fills a research gap by exploring the synergistic effects of these materials, striving to strike a balance between strength and flexibility in soil stabilization. A total of 123 tests, comprising Proctor compaction and unconfined compression tests, were performed on clayey soil samples treated with varying stabilizer proportions: 10%, 20%, and 30% MSWIFA; 10%, 15%, and 20% cement; and 0%, 5%, and 10% rubber by dry weight. The tests revealed that the ideal blend of 5% rubber, 10% MSWIFA, and 20% cement resulted in a notable 294% increase in unconfined compressive strength and a significant enhancement in soil ductility, presenting a stark contrast to traditional cement-stabilized soils recognized for their brittleness and limited flexibility. This approach not only enhances soil characteristics but also promotes environmental sustainability by utilizing waste materials in the stabilization process. Doi: 10.28991/CEJ-2024-010-11-017 Full Text: PDF